TEACHING ADVANCED LISTENING DURING COVID-19 PANDEMIC: LECTURERS’ STRATEGIES EXPLAINED - Saiful Akmal; Mulia Mulia; Ghiffary An-nur (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Listening is one of the four sub-skills in English that need to be mastered. Learning will be more effective when using the appropriate learning strategies. In this pandemic period, appropriate learning strategies are necessary to optimize learning. The purpose of this research is to find out what strategies lecturers need and use in teaching advanced listening during COVID-19 at UIN Ar-Raniry and how lecturers apply and implement the strategy in teaching advanced listening during COVID-19 at UIN Ar-Raniry. The researcher used email and WhatsApp as the media. The data collection method used in this study is qualitative, using a narrative approach. In collecting data, the researcher also used data collection techniques using the semi-structured interview type. The researcher used data reduction and written summarization to analyze the data. The participants are three permanent lecturers and one substitute lecturer in the Department of English Language Education of Ar-Raniry State Islamic University. They are selected purposively using specific criteria. This study’s results indicate that using the right strategy in the learning process will produce effective learning. All participants can investigate their right thoughts, opinions, and arguments, including any aspect of listening teaching strategies.